Mediation of a GDSL Esterase/Lipase in Carotenoid Esterification in Tritordeum Suggests a Common Mechanism of Carotenoid Esterification in Triticeae Species - Requena-Ramírez, María Dolores; Atienza, Sergio G.; Hornero-Méndez, Dámaso; Rodríguez-Suárez, Cristina (Frontiers in Plant Science, 2020)
Carotenoids are essential in human diet, so that the development of programs toward carotenoid enhancement has been promoted in several crops. The cereal tritordeum, the amphiploid derived from the cross between Hordeum chilense Roem. et Schulz. and durum wheat has a remarkable carotenoid content in the endosperm. Besides, a high proportion of these carotenoids are esterified with fatty acids. The identification of the gene(s) responsible for xanthophyll esterification would be useful for breeding as esterified carotenoids show an increased ability to accumulate within plant cells and have a higher stability during post-harvest storage. In this work, we analyzed five genes identified as candidates for coding the xanthophyll acyltransferase (XAT) enzyme responsible for lutein esterification in H. chilense genome. All these genes were expressed during grain development in tritordeum, but only HORCH7HG021460 was highly upregulated. Sequence analysis of HORCH7HG021460 revealed a G-to-T transversion, causing a Glycine to Cysteine substitution in the protein of H290 (the only accession not producing quantifiable amounts of lutein esters, hereinafter referred as zero-ester) of H. chilense compared to the esterifying genotypes. An allele-specific marker was designed for the SNP detection in the H. chilense diversity panel. From the 93 accessions, only H290 showed the T allele and the zero-ester phenotype. Furthermore, HORCH7HG021460 is the orthologue of XAT-7D, which encodes a XAT enzyme responsible for carotenoid esterification in wheat. Thus, HORCH7HG021460 (XAT-7Hch) is a strong candidate for lutein esterification in H. chilense and tritordeum, suggesting a common mechanism of carotenoid esterification in Triticeae species. The transference of XAT-7Hch to wheat may be useful for the enhancement of lutein esters in biofortification programs.